2019
DOI: 10.1016/j.ijcha.2019.100381
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative low-dose rest and stress CT myocardial perfusion imaging with a whole-heart coverage scanner improves functional assessment of coronary artery disease

Abstract: ObjectiveWe evaluated the diagnostic accuracy of myocardial blood flow (MBF) and perfusion reserve (MPR) measured from low-dose dynamic contrast-enhanced (DCE) imaging with a whole-heart coverage CT scanner for detecting functionally significant coronary artery disease (CAD).MethodsTwenty one patients with suspected or known CAD had rest and dipyridamole stress MBF measurements with CT and SPECT myocardial perfusion imaging (MPI), and lumen narrowing assessment with coronary angiography (catheter and/or CT bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Patient 1 CT MPR<2, particularly in the LAD supplied apical segments at both timepoints, were consistent with the impaired hyperemic response documented in the literature as indicative of a functionally significant luminal narrowing≥50% on CT angiography. [21] Patient 2 baseline MPR values were consistent with no hemodynamically significant attenuation of hyperemia as reported by Huang et al [7] Different responses were observed in MPR in Patient 1 when compared to Patient 2 who did not have CAD. A global reduction of MPR, with the range of (1.37-1.8) at follow-up as measured for Patient 2 could now be considered to be indicative of an impaired hyperemic response [7].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Patient 1 CT MPR<2, particularly in the LAD supplied apical segments at both timepoints, were consistent with the impaired hyperemic response documented in the literature as indicative of a functionally significant luminal narrowing≥50% on CT angiography. [21] Patient 2 baseline MPR values were consistent with no hemodynamically significant attenuation of hyperemia as reported by Huang et al [7] Different responses were observed in MPR in Patient 1 when compared to Patient 2 who did not have CAD. A global reduction of MPR, with the range of (1.37-1.8) at follow-up as measured for Patient 2 could now be considered to be indicative of an impaired hyperemic response [7].…”
Section: Discussionsupporting
confidence: 84%
“…[21] Patient 2 baseline MPR values were consistent with no hemodynamically significant attenuation of hyperemia as reported by Huang et al [7] Different responses were observed in MPR in Patient 1 when compared to Patient 2 who did not have CAD. A global reduction of MPR, with the range of (1.37-1.8) at follow-up as measured for Patient 2 could now be considered to be indicative of an impaired hyperemic response [7].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Myocardial Perfusion Reserve (MPR) is the ratio of global myocardial blood flow at stress vs. rest. It is the theoretical gold standard technique for assessing myocardial ischemia in CAD [2]. Although myocardial perfusion can successfully detect and score the CAD, it often deals with some underlying problems due to the technology's nature, such as noise and residual motion.…”
Section: Introductionmentioning
confidence: 99%